Fortifying Democracy: Deploying Electoral Justice for Robust Personal Data Protection in the Indonesian Election - Uu Nurul Huda; Dian Rachmat Gumelar; Alwi Al Hadad (Khazanah Hukum)
Elections stand as a cornerstone of democracy, yet the burgeoning integration of technology and personal data underscores the pressing need for safeguarding individual privacy within the electoral process. This study endeavors to scrutinize the efficacy of the Electoral Justice System in fortifying the protection of personal data throughout the registration, verification, and adjudication phases of political party participation in the forthcoming 2024 elections. Through an empirical juridical methodology, this research delves into the practical application of the Electoral Justice System across diverse national contexts, elucidating its role in mitigating the perils of data misuse and upholding electoral integrity. The findings underscore the imperative of imbuing the Electoral Justice System with structural robustness, substantive fidelity, and a conducive legal culture to ensure the seamless functioning of electoral processes. Additionally, stringent regulations, robust data verification protocols, independent oversight mechanisms, and punitive measures emerge as indispensable facets of effective Electoral Justice System implementation, essential for curtailing infringements of the exploitation of personal data and fostering accountable electoral practices.